Self-Regulated Learning Phases in Interpretive Reading Course: How are They Presented in the Lesson Plan? - Laily Nurjanah, Ratih; Adeoye , Moses Adeleke (Universitas PGRI Semarang, 2023)
This paper aims to provide insight on how Self-regulated learning strategy is implemented in a classroom by presenting how three phases of the strategy; Forethought and Planning phase, Monitoring Performance phase, and Reflection on Performance phase; are shown in the lesson plan of Literal Reading Course at university level to support independent learning skill. This is a case study observing the lesson plan of Literal Reading course in a private university in Central Java, Indonesia. It shows the examples on how each phase of the strategy is realized in the lesson plan considering the aim of the phase which is mentioned to be important to help student become familiar with the course and prepare themselves before joining the sessions of the lecture. Integrating the phases in the lesson plan helps students to be more confident and motivated in joining the lecture since they know what they will face in advance instead of getting sudden materials from the lecturer. It can be inferred that the implementation of the strategy is considered complete by arranging a lesson plan that matches the phases of Self-regulated learning strategy to support the process of Literal Reading learning that is expected to guide students during the lecture.